Relative energy of aluminum hydroxides: The role of electron correlation - Casassa, S.; Demichelis, Raffaella (American Chemical Society, 2012)
The relative energy of aluminum mono- (boehmite and diaspore) and trihydroxides (gibbsite, bayerite, doyleite, and nordstrandite) was investigated with a periodic local Møller-Plesset second-order perturbative approach, with the aim of providing a reliable trend of stability on the basis of a proper description of both the long-range Coulomb interactions and the short-range correlation effects. These components, disregarded in previous studies based on the density functional theory, turn out to be important for these kinds of systems, where hydrogen bonds and van der Waals forces play a fundamental role in stabilizing the structure. The results are in good agreement with the available experimental evidence. The reasons for the monohydroxides energy difference were investigated, with18 diaspore showing an electronic structure for oxygen atoms more favorable than that for boehmite. The problem of the nordstrandite structure was re-examined because of the presence of a second minimum energy structure on the energy surface. Both of them are higher in energy than those of the other trihydroxide polymorphs, and the relative stability of one of these structures with respect to gibbsite is in agreement with recent experimental investigations.